(untitled) (Medicine Today, 2010)
Teaching-learning process involves teacher and learner in a set of dynamic relationship in order to bring positive change in the behavior of learner. To facilitate learning the teacher needs to make teaching in an organized fashion keeping in mind objectives, contents, methods, assessment and sequence of instruction. Some values are to be communicated in the class room which can not be communicated easily by written word. This small article focuses on essential aspects of the subject DOI: 10.3329/medtoday.v22i1.5603 Medicine Today Vol.22(1) 2010. 32-33